How do you solve #6m+n=9# and #m-8n=26# using substitution?

1 Answer

Answer:

#m=2#
#n=-3#

Explanation:

From the given equations
#6m+n=9# first equation
#m-8n=26#second equation

Start with second equation
#m=26+8n#
insert the equivalent in the first equation

#6m+n=9# first equation
#6(26+8n)+n=9# first equation
#156+48n+n=9#
#49n=9-156#
#49n=-147#
#n=-147/49#
#n=-3#

Solve for m now using #n=-3# and #m=26+8n#

#m=26+8n#
#m=26+8(-3)#
#m=26-24#
#m=2#

check:using the original equations
#6m+n=9# first equation
#6(2)+(-3)=9# first equation

#12-3=9#
#9=9#

#m-8n=26#second equation
#2-8(-3)=26#second equation
#2+24=26#
#26=26#

God bless....I hope the explanation is useful.